IDENTIFICATION OF SOCIAL SUPPORT FOR CHILDREN AS SURVIVORS OF DOMESTIC VIOLENCE AT THE SURABAYA EMBUN FOUNDATION - Farah Diba Nur Fanani; Mohammad Zainal Fatah (The Indonesian Journal of Public Health, 2022)
Introduction: Violence is an act that can cause an injury and affects other people both physically and psychologically as opposed to the law. Violence can be considered a crime. In general, violence targets groups or parties that are vulnerable. Children are part of vulnerable groups to violent behavior, including child abuse. According to DPKP3A data, there are 38 children victims of sexual abuse. Methods: This research aims to describe the existence of social support for children as victims of domestic violence at the Embun Surabaya Foundation. This foundation focuses on protecting and empowering children and women who are victims of exploitation and violence. This research used a qualitative approach with phenomenology methods supported by data collection using in-depth interviews and observations. The informants of this research were five people consisting of four girls who were victims of domestic violence and one supervisor staff at the Surabaya Embun Foundation. Result: The results indicate that children as victims of domestic violence at the Embun Surabaya Foundation receive excellent social support in informational support, emotional support, appraisal support, and instrumental support. These four supports have brought victims to accept themselves and increase their confidence. Conclusion: The four supports are given by their families (families that are not included in the perpetrators of violence) and the staff of the Embun Surabaya Foundation. Keywords: Violence, child abuse, social support